Application of Forced Oscillation Technique in Assessing Pulmonary Fibrosis in Hermansky–Pudlak Syndrome - Wilfredo De Jesús-Rojas; Luis Reyes-Peña; José Muñiz-Hernandez; Rolando Mena-Ventura; Gabriel Camareno-Soto; Gabriel Rosario-Ortiz; Marcos J. Ramos-Benitez; Monica Egozcue-Dionisi; Enid Rivera-Jimenez; Rosa Román-Carlo (Advances in Respiratory Medicine)
Hermansky–Pudlak syndrome (HPS) is a rare autosomal recessive disorder characterized by defects in lysosome-related organelles. Given the high mortality rate associated with HPS pulmonary fibrosis (PF) and the significant risks tied to lung transplantation, it is essential to explore new tools for the early surveillance of PF to monitor its progression before clinical symptoms become apparent. This study evaluates the forced oscillation technique (FOT) for assessing PF in five adult patients with HPS, all homozygous for the HPS-1 (c.1472_1487dup p.His497Glnfs*90) founder mutation. Using the Resmon™ Pro V3 device, the FOT measured resistance (Rrs) and reactance (Xrs) at 5, 11, and 19 Hertz (Hz). High-resolution computed tomography (HRCT) scans of the chest were reviewed for radiographic findings. The cohort (n = 5) had a median age of 43 years. All patients exhibited HPS clinical features, including oculocutaneous albinism and respiratory symptoms such as dry cough and dyspnea. Radiographic analysis revealed PF in four patients (80%), with traction bronchiectasis, reticular patterns, honeycombing, and ground-glass opacities. The FOT detected progressive changes in pulmonary resistance and reactance correlating with fibrosis severity. These findings suggest that the FOT is a valuable non-invasive tool for monitoring PF in patients with HPS-1, potentially improving early diagnosis and management.